Pemanfaatan Teknologi Bio-Balitani dalam Optimalisasi Pengolahan Limbah Peternakan di Yayasan Lembu Putih - Dewi N.K.S; N.W.E. Setyawati; P.E.N. Putri; I.M. Wirawan; I.G.A.N.C. Wiguna; I.M. Mudita; I.N.S. Miwada; N.L.G. Sumardani; N.W.T. Inggriati; N.W. Siti (Universitas Mataram, 2022)
The White Lembu Preservation, which is located in Taro Village, Tegallalang District, is one of the places that produces livestock waste which is an indicator of the cause of environmental pollution if it is not managed properly. The service activities carried out are aimed at processing livestock waste, especially cow feces and urine which accumulate into organic fertilizer by disseminating Bio-BaliTani technology. This technology is a multi-use technology based on fermentation technology utilizing superior lignocellulytic probiotic bacteria isolates from the rumen contents of bali cattle and termites. The methods used in this activity are socialization, training, formation of demonstration plots, and mentoring. Bio-BaliTani technology is applied to the processing of livestock manure, feces and urine into organic fertilizer by adding Bio-BaliTani. The results of the activity show that farmers who are members of the Lembu Putih Foundation are able to absorb and apply technology that is well disseminated as indicated by their increased knowledge in the production of solid organic fertilizer and the production of liquid organic fertilizer (biourine). The organic fertilizer produced has been marketed to several hotels in the Tegallalang and Ubud sub-districts. Based on the results of the activity, it can be concluded that the dissemination of Bio-BaliTani technology can be accepted and applied by the Lembu Putih Foundation